Impairment of spermatogenesis and sperm motility by the high-fat diet-induced dysbiosis of gut microbes - Ding, Ning; Zhang, Xin; Zhang, Xue Di; Jing, Jun; Liu, Shan Shan; Mu, Yun Ping; Peng, Li Li; Yan, Yun Jing; Xiao, Geng Miao; Bi, Xin Yun; Chen, Hao; Li, Fang Hong; et al. (Gut, 2020)
ObjectiveHigh-fat diet (HFD)-induced metabolic disorders can lead to impaired sperm production. We aim to investigate if HFD-induced gut microbiota dysbiosis can functionally influence spermatogenesis and sperm motility.DesignFaecal microbes derived from the HFD-fed or normal diet (ND)-fed male mice were transplanted to the mice maintained on ND. The gut microbes, sperm count and motility were analysed. Human faecal/semen/blood samples were collected to assess microbiota, sperm quality and endotoxin.ResultsTransplantation of the HFD gut microbes into the ND-maintained (HFD-FMT) mice resulted in a significant decrease in spermatogenesis and sperm motility, whereas similar transplantation with the microbes from the ND-fed mice failed to do so. Analysis of the microbiota showed a profound increase in genus Bacteroides and Prevotella, both of which likely contributed to the metabolic endotoxaemia in the HFD-FMT mice. Interestingly, the gut microbes from clinical subjects revealed a strong negative correlation between the abundance of Bacteroides-Prevotella and sperm motility, and a positive correlation between blood endotoxin and Bacteroides abundance. Transplantation with HFD microbes also led to intestinal infiltration of T cells and macrophages as well as a significant increase of pro-inflammatory cytokines in the epididymis, suggesting that epididymal inflammation have likely contributed to the impairment of sperm motility. RNA-sequencing revealed significant reduction in the expression of those genes involved in gamete meiosis and testicular mitochondrial functions in the HFD-FMT mice.ConclusionWe revealed an intimate linkage between HFD-induced microbiota dysbiosis and defect in spermatogenesis with elevated endotoxin, dysregulation of testicular gene expression and localised epididymal inflammation as the potential causes.Trial registration number NCT03634644.